Penerapan Hukum Adat dalam Konflik Perkawinan Masyarakat Suku Timor (Dawan Amanuban) di Desa Pollo Kecamatan Amanuban Selatan - Alvintho Tiumlafu; Agustinus Hedewata; Helsina Fransiska Pello (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to: (1) To find out the reason why parties choose customary law in resolving marital problems at Pollo Village, situated in Amanuban Setalan Sub-district, South Central Timor District, (2) To find out the application of customary law enforcement in resolving Tribal marriage issues at Pollo Village, situated in Amanuban Setalan Sub-district, South Central Timor District. This type of this research was Empirical Juridical research, primary data obtained by interviewing 11 respondents and supported by secondary data, qualitative descriptive data analysis. The result of this research is to show that: (1) The way of living of the communities at Pollo Village, situated in Amanuban Setalan Sub-district, South Central Timor District who experience domestic violence conflicts can be settled by custom for the reason that customary law is the result of ancestral heritage that must be maintained and preserved, maintaning unbreakable kinship between local communities, also customary law is considered as fast and affordable. (2) The application of customary law enforcement in resolving marital problem of tribal cummunities at Pollo Village, in Amanuban Setalan Sub-district, South Central Timor District is seen very effective in providing a deterrent effect to perpetrators of domestic violence because the customary sanction imposed are not only punitive but also provide learning for the perpetrators and the local community so that they are afraid and do not be able to commit to the similar action in the future. The practice of customary law enforcement against perpetrators of domestic violence is carried out to correct deviation from obligations and prohibitions in customary community relations, so that the aim is to have a direct impact and direct execution on the violating party. In order to increase the effectiveness of the imposition of customary sanction.